PENINGKATAN HASIL BELAJAR BANGUN DATAR MELALUI MODEL DISCOVERY LEARNING BERBANTUAN CANVA PADA PESERTA DIDIK KELAS IV SDN 21 PARAK KOPI - Meilani Hasibuan, Syakinah; Salmaini Safitri Syam; Yullys Helsa; Salmaini Syofyan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low mathematics learning outcomes of grade IV students at SDN 21 Parak Kopi on two-dimensional figures, with an initial completeness rate of only 16% (class average 55) and a teacher-centered learning process. This study aims to describe the improvement of student learning outcomes on two-dimensional figures through the application of the Canva-assisted Discovery Learning model. The method used is Classroom Action Research (CAR) with a mixed-methods approach (qualitative and quantitative) carried out in two cycles following the Kemmis & McTaggart flow. The research subjects consisted of 25 grade IV students. Data were collected through observation, interviews, documentation, and tests. The results showed a significant overall improvement. The implementation of teacher and student activities increased to 96.8% (Excellent) in cycle II meeting II. Learning outcomes in the knowledge domain increased from an average of 73.72 in cycle I to 91.2 in cycle II, where 22 students successfully achieved the passing grade. The skill domain also increased from an average of 79.32 to 89.33, and the average attitude assessment reached 89.58% at the end of cycle II. It is concluded that the implementation of the Canva-assisted Discovery Learning model is highly effective in improving students' mathematics activities and learning outcomes.